Improving Creativity and Learning Outcomes Through LearningJigsaw on the Islamic Cultural History Subject - Azmiyah, Azmiyah; Rehani, Rehani; Masyhudi, Fauza; Harmonedi, Harmonedi; Trinova, Zulvia; Batubara, Juliana; Illahi, Rilci Kurnia (Ahlussunnah: Journal of Islamic Education, 2025)
There is a tendency for students to receive information passively, low interest in reading, student conditions, and learning approaches.expositorywhich emphasizes verbal delivery of material, resulting in low student learning outcomes in Islamic Cultural History (SKI) learning at MTsN 2 Padang Pariaman. This study aims to determine: 1) changes in learning creativity in the control and experimental classes, 2) improvements in learning outcomes in the control and experimental classes before and after learning with direct learning models and cooperative learning types.jigsaw, 3) a better learning model between cooperative learning models and the type of learning modeljigsawand direct learning models. This study used a quantitative approach with an experimental research method. Data collection techniques included tests, questionnaires, and observations of eighth-grade students at MTsN 2 Padang Pariaman. The analysis results showed that: 1) there was a change in student learning creativity in the class with cooperative learning typejigsaw,2) there is an increase in class learning outcomes with cooperative learning typejigsaw, 3) cooperative learning model typejigsawbetter than direct learning in SKI subjects. The results of this study provide strong empirical evidence for SKI teachers, and teachers of other subjects in general, to integrate the cooperative learning model type.jigsawinto their teaching practice. This model offers an innovative alternative, creating a more interactive and student-centered learning environment, even though the learning modeljigsaw also has limitations.